2019
DOI: 10.3390/genes11010019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Suggests Genes Expressed Stage-Independently and Stage–Dependently Modulating the Wing Dimorphism of the Brown Planthopper

Abstract: Wing dimorphism is considered as an adaptive trait of insects. Brown planthoppers (BPHs) Nilaparvata lugens, a serious pest of rice, are either macropterous or brachypterous. Genetic and environmental factors are both likely to control wing morph determination in BPHs, but the hereditary law and genes network are still unknown. Here, we investigated changes in gene expression levels between macropterous and brachypterous BPHs by creating artificially bred morphotype lines. The nearly pure-bred strains of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previously, the tight junction pathway (KO04530) was found to be enriched in differentially expressed genes across the egg, nymph and adult stages between LW and SW strain BPHs [ 19 ]. In our study, the tight junction pathway was also significantly enriched in the targets of miRNAs highly expressed in the LW strain (adjusted p -value = 1.18 × 10 −2 ) ( Supplementary Table S8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the tight junction pathway (KO04530) was found to be enriched in differentially expressed genes across the egg, nymph and adult stages between LW and SW strain BPHs [ 19 ]. In our study, the tight junction pathway was also significantly enriched in the targets of miRNAs highly expressed in the LW strain (adjusted p -value = 1.18 × 10 −2 ) ( Supplementary Table S8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targets of miRNAs more highly expressed in the LW strain were also enriched in vascular smooth muscle contraction (KO04270, adjusted p -value = 3.80 × 10 −2 ) and the oxytocin signaling pathway (KO04921, adjusted p -value = 1.62 × 10 −2 ) ( Supplementary Table S8 ). Zhang et al [ 19 ] also found that differentially expressed genes between LW and SW strain at the 3rd instar nymph stage were significantly enriched in vascular smooth muscle contraction and the oxytocin signaling pathway. These results imply that the regulation of miRNA expression might be involved in the determination of wing length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA extraction and qPCR methods were referred to by Zhang and Liu (2020). Two reference genes, 18S rRNA and actin were used, because they were stable across conditions (Lin et al ., 2014; Xu et al ., 2015; Xu et al ., 2016; Zhang & Liu, 2020). The primers used in this study are shown in Table S4.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of long‐ and short‐winged lineages of BPH was made according to Zhang and Liu (2020). In brief, for the long‐winged lineage (M♂ × M♀), macropterous females and males with long wings were selected as parents to produce offspring in each generation.…”
Section: Methodsmentioning
confidence: 99%